The role of combination chemo-immunotherapy in advanced non-small cell lung cancer. Issue 7 (3rd July 2019) - Rocco, Danilo; Della Gravara, Luigi; Battiloro, Ciro; Gridelli, Cesare
ABSTRACT: Introduction : Even with the currently recommended chemotherapeutic and immunotherapeutic treatment, the five year survival rate for advanced nonsquamous and squamous NSCLC without oncogenic drivers remains poor. However, several different chemo-immunotherapy combinations are presently being investigated – with favorable results- in order to increase the PFS and OS rates of these patients. Areas covered : Therefore, this paper aims to discuss the most promising trials investigating chemo-immunotherapy combinations and their present and future impact on advanced NSCLC treatment paradigms. Expert opinion : First line chemo-immunotherapy combinations are starting to and will certainly revolutionize the current paradigm of metastatic non small cell lung cancer treatment due to their superior performances – both in terms of PFS and OS – when compared to the actual standard of care platinum based chemotherapy. However, these associations are not devoid of problems, in fact, combining immunotherapy with chemotherapy obviously leads to enhanced treatment-related toxicities and to higher discontinuation rates; therefore these treatments should be administered carefully.